Dampak Aktivitas Masyarakat Terhadap Lingkungan di Terminal Kampung Rambutan - Dyah Ayu Nur Aini; Tasya Maria Agustin Marpaung; Gaitsa Zahira Shafira; Ikhtiar Saputra Aksan; Edward Alfin (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is motivated by the importance of maintaining environmental quality in high-activity public transportation facilities. This study aims to determine the impact of public activities on the environment at Kampung Rambutan Terminal, East Jakarta, focusing primarily on air quality and waste management issues. This study utilizes a qualitative descriptive method through direct field observation techniques and in-depth interviews with terminal managers and workers.The results show that the heavy traffic of motorized vehicles and the ongoing excavation projects around the location cause the air quality around the terminal to fall into the moderate category. Based on IQAir data, the primary pollutant detected is PM2.5 at 27,8 µg/m³. Furthermore, the high activity of passengers and street vendors leads to a significant increase in waste volume, particularly during the peak mudik (exodus) season. Based on interview results, sanitation workers routinely clean the terminal area everyday to maintain environmental cleanliness. This study recommends increasing the frequency of waste collection and planting pollutant-absorbing vegetation.